Facile synthesis of potassium tetrathiooxalate – The "true" monomer for the preparation of electron-conductive poly(nickel-ethylenetetrathiolate). Issue 16 (20th April 2017) - Tkachov, Roman; Stepien, Lukas; Roch, Aljoscha; Komber, Hartmut; Hennersdorf, Felix; Weigand, Jan J.; Bauer, Ingmar; Kiriy, Anton; Leyens, Christoph
Abstract: Herein, aiming at optimization of the polymerization process leading to a family of hole- and electron-conducting 1, 1, 2, 2-ethenetetrathiolate-based polymers, such as poly(nickel-1, 1, 2, 2-ethenetetrathiolate), poly[Kx (Ni-ett)], we investigated transformations of the monomer precursor 1, 3, 4, 6-tetrathiapentalene-2, 5-dione (TPD) occurring under polymerization conditions. We found that only one ring of TPD opens upon its reaction with potassium methoxide under inert conditions at room temperature which leads to the formation of potassium 2-oxo-1, 3-dithiol-4, 5-dithiolate (K2 [3 ]). Heating of K2 [3 ] under reflux in methanol solution under inert conditions opens the second ring, however the resulting product is not potassium ethenetetrathiolate (K4 [2 ]), the product of an exhaustive methanolysis of TPD, but potassium tetrathiooxalate (K2 [4 ]), the product of the decarbonylation of K2 [3 ]. Preliminary experiments reveal that the involvement of K2 [4 ] in the polymerization process is beneficial for reproducible formation of high quality 1, 1, 2, 2-ethenetetrathiolate-based polymers suitable for thermoelectric applications. Graphical abstract: